Stable single helical C-and I-chains inside single-walled carbon nanotubes - 姚震 刘春见 李义 敬晓丹 孟凡顺 郑士鹏 赵星 李久会 邱忠媛 袁泉 王文新 毕磊 刘辉 张玉璞 刘冰冰 (Chinese physics B, 2016)
The helicity of stable single helical carbon chains and iodine chains inside single-walled carbon nanotubes（SWCNTs）is studied by calculating the systematic van der Waals interaction energy.The results show that the optimal helical radius increases linearly with increasing tube radius,which produces a constant separation between the chain structure and the tube wall.The helical angle exhibits a ladder-like decrease with increasing tube radius,indicating that a large tube can produce a small helicity in the helical structures.